Thursday

October 23, 2014

October 23, 2014

Posted by **ann** on Sunday, January 9, 2011 at 9:54pm.

f(x)=2x^2-3x

f(0)=

f(-1)=

f(2)=

- algebra -
**Marth**, Sunday, January 9, 2011 at 9:55pmf(x) = 2x^2-3x

f(0) = 2(0)^2-3(0) = 0

f(-1) = 2(-1)^2-3(-1)

f(2)=?

**Answer this Question**

**Related Questions**

algebra - Give am example of a function f.N N with the property that there ...

College Algebra - 1.Give a quadratic function q(x) with a vertex of (-1, 2). 2. ...

algebra - Determine if the inverse of function {(-3, -6), (-1, 2), (1, 2), (3, 6...

mat 116 algebra - function and function notation using the variable x and ...

Algebra - Rewrite the equation as a function -3x+4y=11 If you want to consider y...

pre calc - The Identity Function The Squaring Function The Cubing Function The ...

College Algebra - Find the inverse of the function below. Graph the function ...

algebra 116 - Rewrite the equation y = 5x – 2 as a function of x. This problem ...

math/prealgebra - what are the actual definitions to the word algebra itself? ...

Algebra - The function f(x)=x 3 +1 4 x−1 4 is a monotonically increasing ...